A high-capacity aqueous all-iron flow battery negative electrode electrolyte
By introducing multifunctional ligand organic molecules into the negative electrode electrolyte of alkaline all-iron flow battery, a stable iron ion complex is formed and the redox activity of the ligand is improved, the problem of poor stability of the electrolyte is solved, and the battery capacity and cycle life are significantly improved.
Patent Information
- Application Number
- CN202410579574.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-05-10
AI Technical Summary
The electrolyte of alkaline all-iron flow batteries has poor stability, resulting in iron ion decomplexation to produce iron hydroxide precipitation, blocking the separator and pipelines, and reducing the battery capacity and cycle life.
Multifunctional ligand organic molecules are introduced into the negative electrode electrolyte to form a stable iron ion complex, and the redox activity of the ligand itself is used to increase the concentration of active substances in the electrolyte.
It improves the battery capacity and cycle life, greatly improving the overall performance of the battery, and the capacity and life are increased by about 30% compared to the existing full iron flow batteries.
Smart Images

Figure CN118738483B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of redox flow batteries, and more specifically, relates to a high-capacity aqueous all-iron flow battery negative electrode electrolyte. Background Art
[0002] With the rapid growth of society's demand for electric energy and the increasing awareness of environmental protection, the use of renewable energy such as solar energy and wind energy has become the focus of attention of countries around the world. However, renewable energy power generation systems have problems such as intermittency and unstable power quality. Therefore, the use of energy storage systems to store unstable and excess renewable energy is considered to have good application prospects. As the most promising chemical energy storage technology, liquid flow batteries can be widely used in wind energy, solar energy and other renewable resource power generation and storage, emergency power supply systems, backup power stations and power system peak shaving. It has the advantages of flexible system design, large storage capacity, high energy conversion efficiency, free site selection, safety and environmental protection.
[0003] The basic components of flow batteries include modules such as electrode materials, electrolytes, diaphragms, storage tanks containing electrolytes, circulation pumps, circulation pipelines, and control systems. The type of flow battery that has achieved commercialization is the all-vanadium flow battery, but its initial investment cost is high, which limits its further large-scale application. In addition to all-vanadium flow batteries, iron-chromium flow batteries, all-iron flow batteries, zinc-bromine flow batteries, and zinc-iron flow batteries are also being studied more. Among them, all-iron flow batteries are divided into all-iron flow batteries in acidic environments and alkaline environments. All-iron flow batteries in acidic environments have solid iron elements participating in the reaction, so they are hybrid flow batteries. Their power and capacity are not completely decoupled, and the advantages of flow batteries are not fully utilized. There is also a more serious hydrogen evolution side reaction.
[0004] The electrolyte of alkaline all-iron flow batteries generally uses iron ion complexes as active substances. Conventional alkaline ligands have weak complexing power and poor stability. After running for a period of time, the pH of the electrolyte changes significantly. The iron ions in the complex decomplex and produce iron hydroxide precipitation, which leads to a series of problems such as blocking the diaphragm ion channel, blocking the pipeline, and incomplete discharge, which ultimately leads to battery capacity decay and is not conducive to the battery's cycle life. In addition, conventional ligands themselves do not have redox activity, but they occupy most of the components in the solution, so the concentration of active substances in conventional electrolytes is low and the capacity is low. Summary of the invention
[0005] In order to solve the technical problems of low capacity and poor stability of the above-mentioned alkaline all-iron flow battery, the present invention introduces multifunctional ligand organic molecules into the negative electrode electrolyte. On the one hand, they can form stable complexes with iron ions in an alkaline environment to extend the battery life; on the other hand, the ligand itself has redox activity, which greatly improves the capacity of the electrolyte.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A high-capacity aqueous all-iron flow battery negative electrode electrolyte, comprising an iron active substance, an active organic ligand, a supporting electrolyte and an auxiliary electrolyte, characterized in that the electrolyte components are all soluble in water, the active substance comprises an iron active substance and an active organic ligand, and the total concentration is 0.1 to 2.0 mol / L. The iron active substance is selected from trivalent iron salts, preferably at least one of ferric chloride, ferric sulfate, ferric phosphate, ferric nitrate and ferric acetate, and the active organic ligand is at least one of 1,3-bis((trihydroxymethyl)methylamino)propane, bis(2-hydroxyethyl)amino(trihydroxymethyl)methane and tris(hydroxymethyl)aminomethane;
[0008] The supporting electrolyte is an alkaline inorganic compound, and the auxiliary electrolyte is selected from inorganic salts that do not participate in the electrochemical reaction. The supporting electrolyte is at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide, and the auxiliary electrolyte is at least one of sodium chloride, potassium chloride, ammonium chloride, sodium sulfate, potassium sulfate, potassium nitrate, and sodium nitrate.
[0009] The concentration of the iron active substance in the electrolyte is 0.1 to 1.0 mol / L, and further, preferably 0.2 to 0.5 mol / L. The concentration of the active organic ligand in the electrolyte is 0.1 to 1.0 mol / L, and further, preferably 0.4 to 0.8 mol / L, and the ratio to the iron active substance is 1:1 to 3:1. The concentration of the supporting electrolyte in the electrolyte is 0.5 to 5.0 mol / L, and further, preferably 1.0 to 3.0 mol / L. The concentration of the auxiliary electrolyte in the electrolyte is 0.1 to 1.5 mol / L.
[0010] The preparation of the electrolyte is to add the iron active substance, active organic ligand, supporting electrolyte and auxiliary electrolyte to oxygen-free deionized water for mixing, and when adding, the iron active substance and supporting electrolyte are added separately using active organic ligand. Preferably, nitrogen is introduced into a closed reactor to exhaust the air, and the iron active substance, active organic ligand, supporting electrolyte and auxiliary electrolyte are added in sequence, and an appropriate amount of oxygen-free deionized water is added before or after the addition of the above substances, and a uniform solution is obtained after constant temperature stirring for a period of time.
[0011] A high-capacity aqueous all-iron flow battery, which consists of electrodes, electrolyte, diaphragm, storage tank, pump and pipeline, etc. The electrodes and electrolyte are divided into positive and negative chambers by the diaphragm, and the electrolyte is transported and circulated by the pump. The operating temperature of the battery is 10-80°C, and the negative electrode electrolyte adopts the above electrolyte. The electrode material is selected from one of carbon felt, graphite felt, graphite plate, graphite paper, carbon paper, and carbon cloth inert materials, and the diaphragm is selected from one of perfluorosulfonic acid proton exchange membrane Nafion117, Nafion115, Nafion212, and Nafion211.
[0012] Compared with the prior art, the present invention has the following significant advantages and beneficial effects:
[0013] In the present invention, a multifunctional ligand organic molecule is innovatively introduced into the negative electrode electrolyte. On the one hand, it can form a stable complex with iron ions in an alkaline environment, so that the redox potential of the iron element shifts toward the negative electrode and matches the positive electrode electrolyte to form a higher voltage; on the other hand, the ligand itself has redox activity, which increases the concentration of active substances in the electrolyte and greatly improves the battery capacity.
[0014] The complex in the negative electrode electrolyte of the present invention has excellent electrochemical activity and stability, and the capacity and life of the flow battery assembled using the electrolyte of the present invention can be increased by about 30% compared with the existing all-iron flow battery. In addition, the raw materials used in the present invention are low in cost, the synthesis method is simple, and it is suitable for supporting energy storage technology for large-scale renewable energy, and has a very broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the cyclic voltammetry curve of the active organic ligand itself in Example 1.
[0016] Figure 2 This is the cyclic voltammetry curve of the negative electrode electrolyte in Example 2.
[0017] Figure 3 The charge and discharge efficiency-cycle curve of the negative electrode electrolyte in Example 2 within 600 cycles.
[0018] Figure 4 The charge and discharge capacity-cycle curve of the negative electrode electrolyte in Example 2 within 600 cycles.
[0019] Figure 5 The energy efficiency of the negative electrode electrolyte in Examples 3 and 4 within 200 cycles. DETAILED DESCRIPTION
[0020] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to these.
[0021] Embodiment 1 (comparative analysis example):
[0022] In this embodiment, the main components of the electrolyte to be tested include: the active organic ligand is 1,3-bis((trihydroxymethyl)methylamino)propane, the supporting electrolyte is sodium hydroxide, the auxiliary electrolyte is sodium chloride, and the solvent is oxygen-free deionized water. The concentration of 1,3-bis((trihydroxymethyl)methylamino)propane is 0.1 mol / L. The purpose of this embodiment is to contrast with the iron-containing negative electrode electrolyte to show that it still has a reversible process of redox reaction in the absence of iron.
[0023] The specific preparation steps of the electrolyte to be tested are as follows:
[0024] In a closed reactor, nitrogen was introduced to exhaust the air, 2.8 g of 1,3-bis((trihydroxymethyl)methylamino)propane, 12.0 g of sodium hydroxide and 2.9 g of sodium chloride were weighed and added in sequence, and an appropriate amount of oxygen-free deionized water was added. After constant temperature stirring for a period of time, a uniform solution was obtained, which was transferred to a 100 mL volumetric flask, protected from light, stored under nitrogen, and allowed to stand for 24 hours before relevant tests.
[0025] The electrochemical test results of the above electrolyte are as follows Figure 1 As shown, the results show that at a scan rate of 50 mV / s, within the appropriate test voltage range, the sample exhibits two pairs of redox peaks, proving that the organic ligand still has redox activity in the absence of iron and that it is a 2-electron transfer process.
[0026] Embodiment 2:
[0027] In this embodiment, the main components of the negative electrode electrolyte include: ferric chloride, 1,3-bis((trihydroxymethyl)methylamino)propane, the supporting electrolyte is sodium hydroxide, the auxiliary electrolyte is sodium chloride, and the solvent is oxygen-free deionized water. Among them, the concentration of ferric chloride is 0.1 mol / L, and the concentration of 1,3-bis((trihydroxymethyl)methylamino)propane is 0.1 mol / L.
[0028] The specific steps for configuring the negative electrode electrolyte are as follows:
[0029] In a closed reactor, nitrogen was introduced to exhaust the air, and 2.7 g of ferric chloride, 2.8 g of 1,3-bis((trihydroxymethyl)methylamino)propane, 12 g of sodium hydroxide, and 2.9 g of sodium chloride were added in sequence. A proper amount of oxygen-free deionized water was added, and the mixture was stirred at a constant temperature for a period of time to form a uniform solution. The solution was transferred to a 100 mL volumetric flask, protected from light, stored under nitrogen, and allowed to stand for 24 hours before relevant tests.
[0030] The above negative electrode electrolyte was subjected to electrochemical testing, and the results are as follows: Figure 2 As shown. At a scan rate of 50 mV / s, the redox peak intensity is significantly enhanced due to the addition of the iron active substance. Compared with the cyclic voltammetry curve of the active organic ligand itself in Example 1, Figure 2 A significantly enhanced oxidation peak and two reduction peaks appeared in the electrolyte, proving the simultaneous existence of redox reactions of iron and active organic ligands in the electrolyte.
[0031] In the single-cell test, the positive electrolyte uses a mixed solution of 0.2 mol / L sodium ferrocyanide and 0.5 mol / L potassium chloride. The components of a single cell include aluminum end plates, polytetrafluoroethylene gaskets, collector plates, graphite bipolar plates, graphite felt electrodes, fluororubber gaskets, and proton exchange membranes. Assemble the single cell and form a battery test system with the positive and negative electrode storage tanks, positive and negative electrode peristaltic pumps, and circulation pipelines. Before testing, fully circulate inert gas in the battery system to avoid inactivation of active substances and deterioration of alkaline electrolytes.
[0032] The volume of positive and negative electrolytes is 20 mL each, and the positive and negative electrodes are 3×3 cm -2 Porous graphite felt electrode, proton membrane is Nafion212 membrane. At 80mA / cm 2 The battery was charged to a cut-off voltage of 1.5V and discharged to a cut-off voltage of 0.8V at a current density of . Figure 3 The efficiency of a single battery after 600 cycles is shown in the figure. During the 600 cycles, the coulombic efficiency (CE) of the battery is always close to 100%, and the voltage efficiency (VE) and energy efficiency (EE) of the battery are generally maintained at around 80%, showing very excellent performance. The corresponding charge and discharge capacity is as follows Figure 4 As shown, the average discharge capacity is about 30% higher than that of other all-iron flow batteries with the same concentration, and maintains good stability.
[0033] Embodiment 3:
[0034] In this embodiment, the main components of the negative electrode electrolyte include: ferric nitrate, bis(2-hydroxyethyl)amino(trihydroxymethyl)methane, the supporting electrolyte is potassium hydroxide, the auxiliary electrolyte is potassium chloride, and the solvent is oxygen-free deionized water. Among them, the concentration of ferric nitrate is 0.2 mol / L, and the concentration of bis(2-hydroxyethyl)amino(trihydroxymethyl)methane is 0.4 mol / L.
[0035] The specific steps for configuring the negative electrode electrolyte are as follows:
[0036] In a closed reactor, nitrogen was passed to exhaust the air, 2.7 g of ferric chloride, 8.4 g of bis(2-hydroxyethyl)amino(trihydroxymethyl)methane, 16.8 g of potassium hydroxide, and 3.7 g of potassium chloride were added in sequence, and an appropriate amount of oxygen-free deionized water was added. After constant temperature stirring for a period of time, a uniform solution was made, which was transferred to a 100 mL volumetric flask, protected from light, stored under nitrogen, and allowed to stand for 24 hours before relevant tests.
[0037] In the battery test, the positive electrode electrolyte used 0.2 mol / L potassium ferrocyanide and 0.5 mol / L potassium chloride solution.
[0038] After the single battery system is assembled, other test conditions are the same as in Example 2.
[0039] Embodiment 4:
[0040] In this embodiment, the main components of the negative electrode electrolyte include: ferric sulfate, tris(hydroxymethyl)aminomethane, the supporting electrolyte is lithium hydroxide, the auxiliary electrolyte is potassium chloride, and the solvent is oxygen-free deionized water. Among them, the concentration of ferric sulfate is 0.2 mol / L, and the concentration of tris(hydroxymethyl)aminomethane is 0.4 mol / L.
[0041] The specific steps for configuring the negative electrode electrolyte are as follows:
[0042] In a closed reactor, nitrogen was introduced to exhaust the air, 8.0 g of ferric sulfate, 4.9 g of tris(hydroxymethyl)aminomethane, 7.2 g of lithium hydroxide, and 3.7 g of potassium chloride were added in sequence, and an appropriate amount of oxygen-free deionized water was added. After constant temperature stirring for a period of time, a uniform solution was made, which was transferred to a 100 mL volumetric flask, protected from light, stored under nitrogen, and allowed to stand for 24 hours before relevant tests.
[0043] In the battery test, the positive electrode electrolyte used 0.2 mol / L potassium ferrocyanide and 0.5 mol / L potassium chloride solution.
[0044] After the single battery system is assembled, other test conditions are the same as in Example 2.
[0045] like Figure 5As shown, although the energy efficiency of the negative electrode electrolyte in Examples 3 and 4 within 200 cycles is slightly lower than that in Example 2, it still maintains very excellent stability.
Claims
1. A high-capacity aqueous all-iron liquid flow battery negative electrode electrolyte, comprising an iron active material, an active organic ligand, a supporting electrolyte and an auxiliary electrolyte, characterized in that: The electrolyte components are all soluble in water, the iron active substance is selected from trivalent iron salt, and the active organic ligand is 1,3-bis((trihydroxymethyl)methylamino)propane.
2. A high-capacity aqueous all-iron liquid flow battery negative electrode electrolyte according to claim 1, characterized in that: The ferric iron salt is selected from at least one of ferric chloride, ferric sulfate, ferric phosphate, ferric nitrate and ferric acetate.
3. A high-capacity aqueous all-iron liquid flow battery negative electrode electrolyte according to claim 1, characterized in that: The molar ratio of the active organic ligand to the iron active substance is 1:1 to 3:1; the total concentration of the iron active substance and the active organic ligand is 0.1 to 2.0 mol / L.
4. A high-capacity aqueous all-iron liquid flow battery negative electrode electrolyte according to claim 1, characterized in that: The supporting electrolyte is an alkaline inorganic compound, and the auxiliary electrolyte is selected from inorganic salts that do not participate in electrochemical reactions.
5. A high-capacity aqueous all-iron liquid flow battery negative electrode electrolyte according to claim 4, characterized in that: The supporting electrolyte is at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide, and the auxiliary electrolyte is at least one of sodium chloride, potassium chloride, ammonium chloride, sodium sulfate, potassium sulfate, potassium nitrate, and sodium nitrate.
6. A high-capacity aqueous all-iron liquid flow battery negative electrode electrolyte according to claim 1, characterized in that: The concentration of the iron active substance in the electrolyte is 0.1-1.0 mol / L; the concentration of the active organic ligand in the electrolyte is 0.1-1.0 mol / L; the concentration of the supporting electrolyte in the electrolyte is 0.5-5.0 mol / L; and the concentration of the auxiliary electrolyte in the electrolyte is 0.1-1.5 mol / L.
7. A high-capacity aqueous all-iron liquid flow battery negative electrode electrolyte according to claim 6, characterized in that: The concentration of the iron active substance in the electrolyte is 0.2-0.5 mol / L; the concentration of the active organic ligand in the electrolyte is 0.4-0.8 mol / L; and the concentration of the supporting electrolyte in the electrolyte is 1.0-3.0 mol / L.
8. A high-capacity aqueous all-iron liquid flow battery negative electrode electrolyte according to claim 1, characterized in that: The preparation of the electrolyte is to add the iron active substance, active organic ligand, supporting electrolyte and auxiliary electrolyte into oxygen-free deionized water and mix them, introduce nitrogen into a closed reactor to exhaust the air, add the iron active substance and active organic ligand, supporting electrolyte and auxiliary electrolyte in sequence, add an appropriate amount of oxygen-free deionized water before or after adding the above substances, and stir at a constant temperature for a period of time to form a uniform solution.
9. A high-capacity aqueous all-iron flow battery, characterized in that: The negative electrode electrolyte adopts the electrolyte described in any one of claims 1 to 8.
10. A high-capacity aqueous all-iron flow battery according to claim 9, characterized in that: It consists of electrodes, electrolyte, diaphragm, storage tank, pump and pipeline. The electrodes and electrolyte are divided into positive and negative chambers by the diaphragm. The electrolyte is transported and circulated by the pump. The operating temperature of the battery is 10-80℃.
11. A high-capacity aqueous all-iron flow battery according to claim 10, characterized in that: The electrode material is selected from one of the inert materials of carbon felt, graphite felt, graphite plate, graphite paper, carbon paper and carbon cloth.
12. A high-capacity aqueous all-iron flow battery according to claim 10, characterized in that: The diaphragm is selected from one of the perfluorosulfonic acid proton exchange membranes Nafion117, Nafion115, Nafion212, and Nafion211.
Citation Information
Patent Citations
Method of determining metal by colorimetry and determination reagent
CN101389954A
Electrolyte of water-based flow battery, all-iron water-based flow battery and application
CN113764714A
Alkaline total-iron flow battery capacity recovery method
CN117650259A